Coal fragmentation studies in a fluidized bed - Pecson, Ferdinand A.
Coal fragmentation experiments were performed in a 0.3m internal diameter by 2.1m high fluidized bed combustor equipped with a solids sampling probe. A 200g batch of 3.0 to 6.9mm coal particles was charged into the hot combustor, and after 90s bed samples were taken at 1 min intervals until burn-off. The samples were immediately quenched with sand, and the burned coal particles were separated from the bed material by screening. Three coals were tested - Texas lignite, Montana sub-bituminous and Colorado bituminous coal. The bed material was 0.4mm silica sand and the fluidizing velocity was 1.8m/s. The effect of reducing the fluidizing velocity to 0.9 m/s and the effect of using 0.8mm aluminum oxide bed material were also investigated. The separated coal particles were sized with a microscope and weighed. Changes in burned coal particle size distribution with residence time were determined and for the case of Montana coal, were compared with the predictions of a combined char burning and attrition model. Microphotographs of the particles were taken to study changes in surface characteristics of the chars.